Minimally invasive approaches for surfactant administration - Trevisanuto, D.; Marchetto, L. (Acta Biomedica Atenei Parmensis, 2013)
Department ofWoman and Child Health, School of Medicine, Padua University, Azienda Ospedaliera di Padova, Padua, Italy Abstract. Respiratory distress syndrome (RDS) is the most common respiratory morbidity in preterm infants. In addition to respiratory support, the current clinical treatment includes endotracheal intubation and rapid instillation of exogenous surfactant. However, this approach needs skilled operators and has been associated with complications such as hemodynamic instability and electroencephalogram abnormalities. New, less invasive methods for surfactant administration are needed. In this article, we reviewed the available noninvasive procedures for surfactant administration. In particular, we focused on aerosolized surfactant and surfactant administration through LMA.